Implementing a national Dutch PEWS system in 12 hospitals with different contexts: opportunities, challenges and implications - Jikke Stevens; Janke de Groot; Joris Fuijkschot; Michèl A Willemsen; Tessa de Jong (BMJ Paediatrics Open)
Background Worldwide, there is a large heterogeneity of Paediatric Early Warning Score (PEWS) systems to detect deterioration in hospitalised children timely. In the Netherlands, the Dutch PEWS was created to enhance national standardisation, incorporating a core set of vital signs and watcher signs with local adaptation strategies. The primary objective of this study was to determine factors for successful implementation. The secondary objectives were to assess the use and perceived value of local adaptation.Methods In a multicentre study, the Dutch PEWS was implemented in 12 hospitals with different contexts ranging from University Medical Centers to general hospitals. This mixed-methods evaluation study prospectively collected data following the Plan-Do-Study-Act cycle. In preparation for implementation, local adaptation was executed, implementation strategies were formulated and baseline measurements were conducted. Post-implementation measures were performed 3, 6 and 9 months after implementation. In total, 1127 questionnaires and 171 interviews were completed with healthcare providers and 11 interviews and 3 member checks with project leaders. The protocol adherence percentage (PAP) was calculated for each hospital as an indicator for implementation.Results The majority of the participants assessed the implementation and use of the Dutch PEWS positively. Important facilitators include reduced workload, increased confidence in achieving the objective and benefits related to utilisation on a national scale. Nationwide use facilitated further integration into training programmes and optimisation of electronic health record systems. At the same time, local adaptation was used in most hospitals and to varying extents. The overall PAP was 81% (±25%), ranging from 47% to 140%.Conclusion This study demonstrates that successful implementation of PEWS systems is related to their design, adaptability to local contexts and nationwide utilisation. Moreover, nationwide use provides opportunities to evaluate the system across diverse contexts, thereby supporting broader implementation.